2016
DOI: 10.1007/s10522-016-9645-9
|View full text |Cite
|
Sign up to set email alerts
|

l-carnosine enhanced reproductive potential of the Saccharomyces cerevisiae yeast growing on medium containing glucose as a source of carbon

Abstract: Carnosine is an endogenous dipeptide composed of β-alanine and l-histidine, which occurs in vertebrates, including humans. It has a number of favorable properties including buffering, chelating, antioxidant, anti-glycation and anti-aging activities. In our study we used the Saccharomyces cerevisiae yeast as a model organism to examine the impact of l-carnosine on the cell lifespan. We demonstrated that l-carnosine slowed down the growth and decreased the metabolic activity of cells as well as prolonged their g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In the present study, CRN enhanced the effect of CoQ on mitochondrial function; thus, the combination of carnosine and CoQ resulted in an increased respiratory reserve capacity and reduced proton leak compared to control or CoQ alone. CRN treatment alone did not show any effect on OCR in HepG2 cells, and previous research has shown that CRN can promote the opposite effect of CoQ upon cellular bioenergetics [ 49 , 50 ]. The synergistic effects seen in the respirometry results also suggest that mitochondria, when the bioenergetic structures are fully saturated with CoQ, may be more responsive to CRN treatment.…”
Section: Discussionmentioning
confidence: 90%
“…In the present study, CRN enhanced the effect of CoQ on mitochondrial function; thus, the combination of carnosine and CoQ resulted in an increased respiratory reserve capacity and reduced proton leak compared to control or CoQ alone. CRN treatment alone did not show any effect on OCR in HepG2 cells, and previous research has shown that CRN can promote the opposite effect of CoQ upon cellular bioenergetics [ 49 , 50 ]. The synergistic effects seen in the respirometry results also suggest that mitochondria, when the bioenergetic structures are fully saturated with CoQ, may be more responsive to CRN treatment.…”
Section: Discussionmentioning
confidence: 90%
“…Recent reports show that carnosine may improve the treatment outcome of aging‐related diseases, such as atherosclerosis, type 2 diabetes, and Alzheimer’s disease 9‐11 . Studies show that carnosine suppresses cell senescence in cultured human fibroblasts 12 and delays aging in senescence‐accelerated mice and drosophila 13‐15 . In addition, some in vitro/in vivo studies using human and animal models show that synthesis of carnosine decreases with age 15 …”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Studies show that carnosine suppresses cell senescence in cultured human fibroblasts 12 and delays aging in senescence-accelerated mice and drosophila. [13][14][15] In addition, some in vitro/in vivo studies using human and animal models show that synthesis of carnosine decreases with age. 15 Recent research reports that carnosine can alleviate aging-related vascular diseases, such as atherosclerosis and type 2 diabetes.Vascular calcification is a complication that also occurs during aging,…”
mentioning
confidence: 99%